Deciphering the Heteropterys pannosa species complex (Malpighiaceae) - André M. Amorim; Lucas C. Marinho; Augusto Francener (PeerJ, 2022)
We describe three new species of Malpighiaceae that are endemic to central Brazil and related to the Heteropterys pannosa complex, a group of xylopodiferous, unbranched subshrubs with fruit in mericarps that have a strongly reduced or no dorsal wing. Heteropterys tocantinensis is more common in eastern Tocantins State and on the border with Bahia State, and there are a few records from Mato Grosso State. Heteropterys veadeirensis is restricted to northern Goiás State and H. walteri has a wider distribution, occurring in some municipalities in northern Goiás and southern Tocantins. Additionally, we also provide detailed redescriptions of H. pannosa and H. rosmarinifolia, the two previously known species in this complex. All species are considered Endangered (EN) based on IUCN criteria, especially due to the low area of occupancy. Illustrations, distribution maps, and information about phenology and habitat are also provided for all taxa.